Fiscal and financial conditions for a stronger euro area - Vítor Constâncio (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2020)
The euro is irreversible but it needs reform to address well-known design deficiencies and also new challenges. Although progress has been made, further steps are needed, the most important of which are: revision of the fiscal rules, establishing a central stabilisation capacity, and completing the banking union (especially a deposit insurance, a capital market union based around a common safe asset, and improved macroprudential policy). This article sets out the necessary reforms in these areas in detail.
Keywords: E02; E50; E60; O52; 330; EMU reform; fiscal rules; Stability and Growth Pact; European safe asset